Beyond the fear that lingers : the interaction between fear of cancer recurrence and rumination in relation to depression and anxiety symptoms - Liu, Jianlin (2020)
The Fear of Cancer Recurrence (FCR) is reported to be a normal response to cancer, but little is known about the interaction between FCR and maladaptive cognitive processes, which may increase the risk for depression and anxiety disorders among cancer survivors. Previous studies have shown the influence of rumination on depression and anxiety in other populations. Thus, the present study aimed to examine how FCR and rumination may relate to depression and anxiety symptoms among cancer survivors.